2018
DOI: 10.1038/s41420-018-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

SLC2A5 promotes lung adenocarcinoma cell growth and metastasis by enhancing fructose utilization

Abstract: The metabolism of cancer cells is highly plastic. Cancer cells can change their preference for nutrient uptake under nutrient stress. Fructose is one of the most common carbohydrates in diet and its metabolism is also involved in the development and progression of tumors. GLUT5, encoded by SLC2A5, is the specific fructose transporter in mammalian cells. In this study, we found that SLC2A5 is significantly upregulated in lung adenocarcinoma (LUAD) patients and overexpression of SLC2A5 is highly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…In addition, it has been found that the glucose transporter GLUT1 is highly expressed in the primary lung cancer, but the fructose transporter GLUT5 is highly expressed in the metastasis, suggesting that fructose plays an important role in the metastasis of lung cancer. 15 From all the results, we found that fructose could be used by ovarian cancer cells, and GLUT5 was necessary for this utilization. GLUT5 was expressed at a significantly higher level in ovarian cancer tissues, and its higher expression was correlated with malignant progression, and poor survival of patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, it has been found that the glucose transporter GLUT1 is highly expressed in the primary lung cancer, but the fructose transporter GLUT5 is highly expressed in the metastasis, suggesting that fructose plays an important role in the metastasis of lung cancer. 15 From all the results, we found that fructose could be used by ovarian cancer cells, and GLUT5 was necessary for this utilization. GLUT5 was expressed at a significantly higher level in ovarian cancer tissues, and its higher expression was correlated with malignant progression, and poor survival of patients.…”
Section: Discussionmentioning
confidence: 84%
“…17,25 GLUT5, as a specific fructose transporter in mammalian cells, has also been found highly expressed in breast cancer, glioma, lung cancer and so on, and silencing GLUT5 could significantly inhibit these cancer cells growth in fructose medium. 13,[15][16][17][18]23 In this study, we used a similar method to silence GLUT5 in ovarian cancer cells to explore the role the GLUT5 in fructose metabolism in ovarian cancer. As expected, silencing GLUT5 could significantly inhibit the abilities of proliferation, colony formation, and migration in fructose medium, which suggested that GLUT5 was necessary for fructose utilization in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed that SLC2A5 ‐mediated fructose utilisation might play an important role in cancer cell growth and survival (Chen et al , ; Weng et al , ). In our study, the addition of fructose protected SUP‐B15 cells from nutrient deficiency‐induced cell death (Fig A, B).…”
Section: Resultsmentioning
confidence: 99%
“…SLC2A5 encodes SLC2A5 (previously termed GLUT5), which belongs to the glucose transporter proteins family, and facilitates fructose uptake by cells (Barron et al , ). Previous research showed that SLC2A5 was upregulated in various human cancers, such as breast cancer (Macheda et al , ), renal carcinoma (Medina Villaamil et al , ), lung cancer (Weng et al , ) and leukaemia (Chen et al , ). The leukaemia study showed that SLC2A5 promoted acute myeloid leukaemia (AML) fructose utilisation and chemoresistance (Chen et al , ).…”
mentioning
confidence: 99%